The Effect of Inflation, Interest Rates and Exchange Rates on Stock Prices of Manufacturing Companies in Basic and Chemical Industrial Sectors on the Indonesia Stock Exchange (IDX) - Jefry, Jefry; Djazuli, Abid (International Journal of Business, Management and Economics, 2020)
This study examines the effect of inflation, interest rates and exchange rates on stocks in basic industrial sector and chemical manufacturing companies on the Indonesia Stock Exchange (BEI). The study period is 2013 to 2017. An ordinary least square (OLS) is employed. The results show that (1) There is a significant effect of inflation, interest rates and exchange rates on stocks. together with the Basic Industry and Chemical Sector Manufacturing companies on the Indonesia Stock Exchange (IDX); (2) There is a significant influence of inflation on shares in manufacturing companies in the Basic Industry and Chemical Sector on the Indonesia Stock Exchange (BEI); (3) There is no significant effect of interest rates on stocks in basic industrial sector and chemical manufacturing companies on the Indonesia Stock Exchange (BEI); (4) There is no significant effect of Exchange Rates on Shares in Basic Industry and Chemical Manufacturing companies on the Indonesia Stock Exchange (IDX).